Asessment of genetic diversity of Vietnam rice by ssr markers to identify cross combinations for development of drought tolerant rice cultivars - Bich Huyen, Vu Thi; Bich Thuy, Le Thi; Dung, Nguyen Anh; Tien, Hoang Ba; Thanh, Nguyen Duc (Academia Journal of Biology, 2013)
SSR (simple sequence repeat) are the markers of high polymorphism and stability, which are widely used in studying the genetic diversity of rice. In this study, we present results on the use of 22 SSR primer pairs to analyze the genetic diversity of 75 rice lines, in an attempt to identify cross combinations for the development of drought tolerant rice cultivars. All 22 primer pairs gave polymorphisms with 90 alleles, alleles number of each SSR primer pairs ranged from 2 to 8 and an average value is 4,09. Polymorphic information contents (PIC) of used primer pairs ranged from 0.026 (RM308) to 0.776 (RM547). The heterozygosity coefficient (H) of the investigated rice lines were rather low: 70 lines have H’s value ranged from 0% to 9.09%; only 5 lines have H’s value more than 10%. There were 16 rare alleles on 13 primer pairs. Genetic similarity coefficient ranged from 0.026 to 0.826, and 75 lines divided into 2 groups. Based on results of genetic diversity and drought characteristics of 75 rice lines, 8 cross combinations which could be useful for the development of drought tolerant rice were proposed.